2016
DOI: 10.1021/acsami.6b04176
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Highly Selective Drug Optosensing in Real, Undiluted Biological Samples with Quantum-Dot-Labeled Hydrophilic Molecularly Imprinted Polymer Microparticles

Abstract: Quantum-dot (QD)-labeled hydrophilic molecularly imprinted polymer (MIP) microparticles were prepared for direct and highly selective optosensing of an antibiotic drug (i.e., tetracycline (Tc)) in pure bovine/goat milks and bovine/porcine serums. "Living" CdTe QD-SiO2 composite microparticles with alkyl bromide groups on their surfaces were first obtained via the one-pot sol-gel reaction, and they were subsequently grafted with a Tc-imprinted polymer layer and poly(glyceryl monomethacrylate) brushes via the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Besides, it was possible to remove Tc from the biological medium directly, precisely, selectively and in a yield of 95% -105% by the MIP-based chemosensor prepared. In these measurements, it was observed that Tc did not interfere with other drugs [103]. Niu et al in the same group suggested a different method for the efficient determination of Tc.…”
Section: Mass-sensitive Biosensorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides, it was possible to remove Tc from the biological medium directly, precisely, selectively and in a yield of 95% -105% by the MIP-based chemosensor prepared. In these measurements, it was observed that Tc did not interfere with other drugs [103]. Niu et al in the same group suggested a different method for the efficient determination of Tc.…”
Section: Mass-sensitive Biosensorsmentioning
confidence: 97%
“…Polymeric brushes have advantages such as interfacial localization of terminal groups, diffusion control, regulation of steric repulsive forces, control of phase-segregation in response to external stimuli, wetting control, control of protein and cell adsorption, adsorption of molecules, lubrication, and flocculation control [98]. In these measurements, it was observed that Tc did not interfere with other drugs [103]. Niu et al in the same group suggested a different method for the efficient determination of Tc.…”
Section: Mass-sensitive Biosensorsmentioning
confidence: 99%
“…For organic MIPs, surface hydrophilicity modification is necessary. Zhang [70][71][72][73][74][75][76][77][78][79] proposed a strategy to graft hydrophilic polymer brush on the surface of spherical MIPs. Generally, spherical MIPs were first prepared by living precipitation polymerization (RAFTPP 71,73,74 or ARTPP 72 ), then hydrophilic polymer brushes were grown in situ on their surfaces by surface initiated living polymerization.…”
Section: Spherical Mips With Polymer Brushmentioning
confidence: 99%
“…The MIFs have been widely used in food quality and safety analysis. Most of the studies focus on the fluorescence detection of agricultural and veterinary drug residues [9,84], drug residues [85], prohibited additives [86], heavy metals, environmental organic pollutants, and other hazard factors.…”
Section: Application Of Mifs In Food Quality and Safety Detectionmentioning
confidence: 99%